2018
DOI: 10.2319/030918-195.1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of bracket survival and adhesive removal time using flash-free or conventional adhesive for orthodontic bracket bonding: A split-mouth randomized controlled clinical trial

Abstract: Objectives: To compare bracket survival and adhesive removal time between a flash-free and a conventional adhesive for orthodontic bracket bonding. Materials and Methods: Forty-five consecutive patients had their maxillary incisors, canines, and premolars bonded with ceramic brackets using a flash-free adhesive (APC Flash-Free Adhesive, 3M Unitek, Monrovia, Calif) on one side and a conventional adhesive (APCII Adhesive, 3M Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 17 publications
1
53
1
Order By: Relevance
“…2)Operator-Related Variables -bonding protocol and bonding materials. Once bonding failure occurs, the attachment will detach from the tooth in a short time [14].…”
Section: Discussionmentioning
confidence: 99%
“…2)Operator-Related Variables -bonding protocol and bonding materials. Once bonding failure occurs, the attachment will detach from the tooth in a short time [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to shorter chair time, adequate bond strength and shorter clean-up time, the possibility of better oral hygiene owing to the protective effects of the adhesive and the decrease in retentive sites for plaque accumulation, are favorable aspects of flash-free brackets. [2][3][4] In a first clinical and microscopic study, Foersch et al 2 reported that smooth marginal surfaces of the adhesive in flash-free brackets might provide a protective effect against demineralization around the bracket sides. On the other hand, Jung et al 5 emphasized that the movement of flash-free brackets on the tooth's surface might increase plaque accumu-lation caused by a gap in the direction of slip during the bracket positioning process.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] A recent clinical study concluded that flash-free brackets shortened the debonding time by allowing the adhesive remnant material on the enamel surface to be cleaned more easily at the end of the treatment. 5 However, a limited number of studies on this topic have been carried out. [5][6][7] Another issue of concern to orthodontic patients is the amount of pain experienced during the debonding procedure.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, a limited number of studies on this topic have been carried out. [5][6][7] Another issue of concern to orthodontic patients is the amount of pain experienced during the debonding procedure. Many previous studies evaluated pain during debonding, but they were frequently focused on a specific technique or method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation